Mapping Montale's autographs. Around the conference for the Fondo Manoscritti of the University of Pavia (3rd and 4th April 2019) (Prassi Ecdotiche della Modernità Letteraria, 2019)
On 3rd and 4th April 2019 in Pavia, in the Teresian Hall of the University Library, took place the convention celebrating the 50 years of the founding of the "Fondo Manoscritti".  A detailed summary can be found in this contribution.